Pergamon, Türkei. Neue Forschungen zum Pitanedossier aus Pergamon. Ein Arbeitsbericht der Jahre 2018 bis 2021 - Schneider, Julian (e-Forschungsberichte des DAI, 2021)
The so-called Pitane Dossier from Pergamon documents a case of interstate arbitration in a territorial dispute on the western coast of Asia Minor, involving the cities of Pitane and Mytilene. Containing two decrees and an arbitral award, the dossier sheds light on the preliminary negotiations, the judicial procedure, and the final decision by five Pergamene judges. In the course of recent epigraphic fieldwork in Pergamon since 2016, three unpublished fragments had been identified as pertaining to this inscription. This substantial progress provided a strong incentive to re-edit the whole monument, including the already known fragments, and to accompany the new textual edition with a systematic commentary.